A clinical perspective on regional nodal irradiation for breast cancer. (August 2017) - Moreno, Amy C.; Shaitelman, Simona F.; Buchholz, Thomas A.
Abstract: The goal of regional treatments in breast cancer should be to eradicate any disease within lymph nodes, avoid regional recurrences, minimize the risk of distant metastases, and improve survival. In addition, regional treatments should focus on reducing potential morbidities and optimizing the long-term quality of life of breast cancer survivors. While data from recent surgical and radiation trials have helped clarify many issues regarding regional treatment, there still remains controversy as to the optimal approach for patients with "intermediate risk" disease. Two large radiation oncology studies (MA.20 and EORTC2292-10925) evaluated whether more extensive lymphatic treatment benefited patients with higher-risk lymph node-negative, or lower risk lymph node-positive disease. A meta-analysis of these two studies suggested that the addition of regional nodal irradiation (RNI) to the level III axillary, supraclavicular and upper internal mammary lymph nodes conferred an improvement in disease free survival and distant metastasis free survival as well as a 1–2% overall survival advantage. However, other studies have suggested that many patients with positive sentinel lymph nodes who are treated with breast conservation including breast irradiation may safely avoid the morbidity and costs of further axillary treatment (whether surgical or radiotherapy-based). In general, patients with 1–3 positive lymph nodes or high-risk, node negative stage II breast cancer represent a diverse population who require individualized, rather than group-based, risk assessment when considering RNI. This article will propose a strategic methodology to assess the modern day breast cancer patient's need for RNI in the setting of changing surgical, radiation, and systemic therapies. Highlights: Radiation provides a significant survival benefit for locally advance breast cancer. The role and extent of regional nodal irradiation for stage II disease is unclear. A systematic algorithm is proposed when considering regional nodal irradiation.